Hubungan Riwayat Pemberian ASI Eksklusif dan MP-ASI dengan Kajadian Stunting pada Balita di wilayah Kerja Puskesmas Kampa - Sriwidya Astuti Khati; Adelia Nopriyarti; Ade Yelda Hastriarti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Stunting is a phenomenon of growth impairment experienced by infants and young children under 5 years of age, particularly toddlers aged 0–59 months. Based on Global Prevalence Data, approximately 21.9% to 22% of toddlers worldwide experience stunting. Several factors that contribute to stunting include breastfeeding and complementary feeding (MP-ASI) practices. This study aims to explore the association between experiences of exclusive breastfeeding and complementary feeding (MP-ASI) and the incidence of stunting among children in the Kampa Community Health Center area. The method used in this study was a cross-sectional approach. The study was conducted during the period of January 8–13, 2024, at the Kampa Community Health Center, involving toddlers aged 6–59 months, with a population of 1,576 toddlers. The sample consisted of 68 mothers who had stunted toddlers, measured using a height-for-age (H/A) Z-score of less than -2 standard deviations (SD). The sampling technique applied was total sampling. Data collection was carried out using a microtoise and questionnaires. Data analysis was performed using the Chi-square method. The findings showed a significant relationship between a history of exclusive breastfeeding and the incidence of stunting with a P value of 0.00 < 0.05, as well as a significant relationship between exclusive complementary feeding (MP-ASI) and the incidence of stunting in toddlers with a P value of 0.04 < 0.05. It is recommended that health workers organize counseling classes on lactation and conduct demonstrations on how to prepare complementary foods (MP-ASI), focusing on the use of affordable local food ingredients that are rich in animal protein. In addition, continuous training for community health cadres needs to be carried out to improve early detection through accurate anthropometric measurements, so that toddlers at risk of stunting can be promptly managed.